2022
DOI: 10.1021/acsaelm.1c01296
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic Epitaxial Integration of β-Ga2O3 with 100 Si for Deep Ultraviolet Photodetectors

Abstract: In this report, we demonstrate direct epitaxial integration of β-Ga 2 O 3 on a (400) oriented silicon on insulator substrate toward deep-UV (DUV) optoelectronics. The 550 nm thick (400) epitaxial-β-Ga 2 O 3 films are deposited onto Si(100) using a two-step buffer and a two-step epilayer scheme. The epitaxial orientation relation between β-Ga 2 O 3 , MgO, and silicon( 100) is given by (400The presence of rotational variants is confirmed by Xray diffraction and transmission electron microscopy. Epitaxy was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Solar-blind ultraviolet (SBUV) photodetectors have broad application prospects in military and civil fields such as missile warning, space security communications, environmental monitoring, and fire monitoring due to their low background noise, high sensitivity, and strong anti-jamming ability. [1][2][3] In recent years, owing to the unique advantages of all-solid state, small size, intrinsic solar blindness, high thermal and chemical stability, strong radiation resistance, and low energy consumption, SBUV photodetectors fabricated from wide-bandgap semiconductors including AlGaN, [4][5][6][7] Ga 2 O 3 [8][9][10][11][12][13] and ZnMgO, [14][15][16] have attracted significant attention and are generally considered to be the next generation of UV photodetectors. However, the preparation of high-quality AlGaN with high Al composition suitable for solar-blind detection still faces many challenges due to the significant lattice and thermal mismatches between the AlGaN layer and the hetero-substrate and the high surface migration barrier of Al atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Solar-blind ultraviolet (SBUV) photodetectors have broad application prospects in military and civil fields such as missile warning, space security communications, environmental monitoring, and fire monitoring due to their low background noise, high sensitivity, and strong anti-jamming ability. [1][2][3] In recent years, owing to the unique advantages of all-solid state, small size, intrinsic solar blindness, high thermal and chemical stability, strong radiation resistance, and low energy consumption, SBUV photodetectors fabricated from wide-bandgap semiconductors including AlGaN, [4][5][6][7] Ga 2 O 3 [8][9][10][11][12][13] and ZnMgO, [14][15][16] have attracted significant attention and are generally considered to be the next generation of UV photodetectors. However, the preparation of high-quality AlGaN with high Al composition suitable for solar-blind detection still faces many challenges due to the significant lattice and thermal mismatches between the AlGaN layer and the hetero-substrate and the high surface migration barrier of Al atoms.…”
Section: Introductionmentioning
confidence: 99%
“…The rejection ratio as a function of responsivity has been also benchmarked in figure 6(b). The developed MSM detectors in this work exhibit high rejection ratios over 10 5 , which are on the frontier of the reported Ga 2 O 3 MSM solar-blind detectors [28,30,32,[47][48][49][50][51][52][53][54][55][56]. Further improvement of material quality and structural design are undergoing.…”
Section: Resultsmentioning
confidence: 99%
“…Epitaxial β-Ga 2 O 3 (2̅01) on Si (001) has been demonstrated with γ-Al 2 O 3 and YSZ buffer using molecular beam epitaxy (MBE) and pulsed laser deposition (PLD), respectively. We (Vura et al) have previously demonstrated β-Ga 2 O 3 (400) on Si (100) using MgO buffer for deep UV photodetectors. These buffers, however, are electrically insulating, and hence, vertical power devices require additional conducting layers such as SrRuO 3 or LaNiO 3 , increasing the complexity.…”
Section: Introductionmentioning
confidence: 99%